ADM in Public Administration in Finland and Hungary: Does the Legal Culture Matter? - Mäntylä, Niina; Barta, Attila; Karjalainen, Ville (Wolters Kluwer, 2025)
The digital transformation of the public sector and automation of decision-making (ADM) processes have recently become common. Its goal usually is to make public administration more effective, competitive and trusted. At the same time, especially the use of AI-based automation in the public sector contains many risks. In this article, we will focus on the legal solutions related to these risks, in two European countries, Finland and Hungary. Does the legal culture have an influence on the solutions how the risks have been controlled? Finland represents the Nordic legal culture. Despite this quite homogeneous legal culture in general, attitudes towards ADM related legislation differ. In some countries, such as in Sweden, the increased interest towards ADM/AI has led only minor legislative changes to the administrative law framework, when in Finland different path with a stricter restrictions and detailed legislation have been chosen. East Central Europe is as little homogeneous as the Nordic countries what comes to the attitudes towards ADM and AI. It seems that the Europeanization plays a greater role than the historical divisions protecting important values such transparency and accountability in the context of ADM. As a result, Finland, as well as Hungary, represent countries which have developed legal safeguards for the use of ADM detailed way. Nonetheless, it is important to note that in areas of broader national discretion, such as national security, current challenges are testing the values of even traditionally strong rule-of-law states, such as Finland.
Keywords: Automated decision making; legal culture (Finland, Hungary); Europeanization; public administration; Nordic countries; East Central Europe; administrative law; human intervention; AI (EU); legal safeguards; fi=Julkisoikeus|en=Public Law|; fi=Julkisoikeus|en=Public Law|